2018
DOI: 10.1016/j.forsciint.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Establishing state of motion through two-dimensional foot and shoe print analysis: A pilot study

Abstract: Background: The aim of this study was to determine whether toe sliding is more likely to cause knee injuries than flatfoot sliding in curling. Methods: Twelve curlers participated in the study, each delivering stones. Six stones per volunteer were delivered using a flatfoot slide and 6 were delivered using a toe slide. The Pedar-X inshoe pressure system recorded the plantar pressure present during each of the slides, while a sagittal plane digital video recorded the body position of the curler. Measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…[13] reported a similar finding where footprint lengths were shown to be greater in walking compared to a standing state. This was also reported by Neves et al [10] who found walking and running footprint lengths to be larger than standing footprint lengths. However, foot elongation may not fully explain this difference, as Vernon et al [14] suggests ghosting in dynamic footprints may contribute to greater length measurements resulting from the backward splaying of the heel's fibro-fatty pad and from curvature of the toe apices rolling off the supporting surface.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…[13] reported a similar finding where footprint lengths were shown to be greater in walking compared to a standing state. This was also reported by Neves et al [10] who found walking and running footprint lengths to be larger than standing footprint lengths. However, foot elongation may not fully explain this difference, as Vernon et al [14] suggests ghosting in dynamic footprints may contribute to greater length measurements resulting from the backward splaying of the heel's fibro-fatty pad and from curvature of the toe apices rolling off the supporting surface.…”
Section: Discussionsupporting
confidence: 84%
“…This may explain why mean walking footprint length (255.4mm) was smaller, compared to our study (268.61mm), as females have predominantly smaller feet [7,33]. Similar issues also affect findings reported by Neves et al [10] as their sample was composed of six male and five female participants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…62 Where footprint measurement research has included both left and right feet, asymmetry has been noted in most publications. 23,56,[63][64][65][66][67][68] Burrow noted in a limited study of sixteen participants, where four footprints were collected from each subject, that there were no significant differences in footprint size and shape between those collected in the morning and those collected in the afternoon. 69 These results have implications for forensic practice as they suggest that the timing of reference print collection can be flexible during forensic practice.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, differences have been established between standing and walking inked bare footprints collected under controlled conditions with males reported to have a mean intravariation of 18 mm for the first toe to heel measurement. 55,56 Neves et al 56 found that running footprints were larger than static footprints but smaller than walking footprints. In a pilot study, Nirenberg et al 57 determined that there were no significant statistical differences between socked footprints and inked bare footprints, and also between insole foot marks and inked bare footprints.…”
Section: Introductionmentioning
confidence: 99%